AB0806 Polymorphisms Analysis of Bone Metabolism Genes in Relation to Bone Mineral Density in Patients with Chronic Periodontitis. (10th June 2014) - Lakhdar, T.; El jaoudi, R.; Ibrahimi, A.; Ennibi, O.K.; Znat, F.; Allali, F.; Rkain, H.; Hajjaj-Hassouni, N.
Abstract : Background: Polymorphisms in Vitamin D receptor (FokI (VDR-F) and BsmI (VDR-B)), Estrogen receptor (Pvu II (ESR1P) and Xba I (ESR1X)), Collagen type1 (SpI (COL1A1) and Calcitonin Receptor (Alu I (CTR)) are thought to be candidate markers for osteoporosis. Based on the fact that osteoporosis and periodontal diseases are bone destructive diseases, we investigated the relationship between polymorphisms in these candidate genes and bone mineral density (BMD) of lumbar spine and femoral neck in patients suffering from chronic periodontitis (CP). Methods: Lumbar spine and femoral neck BMD of individuals included in this study were diagnosed using the dual X-ray absorptiometry method. Blood was drawn and Genomic DNA was prepared and genotyped using MetaBone Clinical Arrays kit (Genomica, Spain). The genotyping and polymorphisms identification consisted on the simultaneous amplification of five regions of the genome containing the six SNPs of interest. Clinical attachment level (CAL), gingival bleeding index (GI), and probing depth (PD) and Simplified Oral Hygiene Index (OHI-S) were determined in all participants by a single experimented examiner. Results: Table 1 (below) shows SNPs and variant alleles prevalence of genes associated with metabolic bone disorders in 18 chronic periodontitis patients: Statistical analysis showed that women with CP carrying the genotype VDRF-FOKI (Ff) have a lower lombar BMD (p=0.003) and higher number of teeth loss (p=0.003). However, we were not able, in this preliminary study, to show any association between BMD of lumbar spine L2–L4 and Ward's BMD in CP patients and polymorphisms in different geotyped genes; Vitamin D receptor BsmI (VDR-B), Estrogen receptor PvuII (ESR1P), Collagen type1 SpI (COL1A1) and Calcitonin Receptor Alui (CTR). Furthermore, no association was found between these polymorphisms and severity parameters of chronic periodontitis. Conclusions: This preliminary study showed that Lower lombar BMD were observed in patients who carried VDRF-FOKI Ff genotype and lower prevalence of normal variants of VDRB-BSMI, CTR-ALUI and ESR1X-XBAI in the population of chronic periodontitis women. A larger case control study is ongoing in order to get bigger data to complete this report. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5961